The Application of Optical Coherence Tomography Angiography in Systemic Hypertension: A Meta-Analysis - Tan, Wilson; Yao, Xinwen; Le, Thu-Thao; Tan, Anna C. S.; Cheung, Carol Y.; Chin, Calvin Woon Loong; Schmetterer, Leopold; Chua, Jacqueline (Frontiers in Medicine, 2021)
Objective: Multiple studies have compared various optical coherence tomography angiography (OCTA) parameters in participants with systemic hypertension versus controls and have presented discordant findings. We conducted a meta-analysis to pool together data from different studies to generate an overall effect size and find out whether OCTA parameter(s) significantly differed in participants with systemic hypertension as compared to controls. Methods: We conducted a literature search through a search of electronic databases to identify studies before 19 June 2021, which compared OCTA parameters in non-diabetic participants with systemic hypertension versus controls. If the OCTA parameter had a minimum number of 3 studies that analyzed it, the mean difference between participants with systemic hypertension and controls were analyzed using a random-effects model. Results: We identified 11 eligible studies. At the macula, 9 studies analyzed vessel density at the superficial capillary plexus (SVD), 7 analyzed vessel density at the deep capillary plexus (DVD), and 6 analyzed the area of the superficial foveal avascular zone (FAZ). Participants with systemic hypertension had significantly lower SVD (standardized mean difference [SMD], -0.50 [-0.70, -0.30], P < 0.00001, I² = 63%), lower DVD (SMD, -0.38 [-0.64, -0.13], P=0.004, I² = 67%) and larger superficial FAZ (SMD, 0.32 [0.04, 0.61], P=0.020, I² = 77%). Conclusion: The eyes of people with systemic hypertension have robustly lower superficial and deep vascular densities at the macula when compared to control eyes. Our results suggest that OCTA can provide information about pre-clinical microvascular changes from systemic hypertension.